MicroRNA in intestinal tight junction regulation - Manmeet Rawat; Prem Kumar Govindappa; Yash Gupta; Thomas Y. Ma (npj Gut and Liver)
Abstract MicroRNAs are essential molecules that regulate many biological functions, including intestinal tight junction (TJ) barriers. They regulate pro-inflammatory cytokines, which increase TJ permeability, and anti-inflammatory cytokines, which protect against inflammation and promote intestinal balance. This review explores the role of miRNAs in controlling inflammation and as a potential therapeutic approach for treating IBD and other intestinal disorders. Circulating miRNAs can also serve as biomarkers for intestinal damage and disease progression.